P-181 Association of DHCR7/NADSYN1-rs12785878 and GC-rs7041 Polymorphism with Serum 25-Hydroxyvitamin D Levels in Singapore Chinese IBD Patients. (March 2016) - Ong, Wan Chee; Wan, Choon Nam; Valerie Ng, Yun Ting; Ho, Choon Siang; Lim, Teong Guan; Webber Chan, Pak-Wo; Kong, San Choon; Ling, Khoon Lin; Ong, Pei Shi
Abstract : Background: Inflammatory bowel diseases (IBD) are chronic, inflammatory disorders of the gastrointestinal tract with unclear etiology. Vitamin D (VitD) has been implicated with IBD development and its supplementation had resulted in improvement in IBD disease activity. In recent genome wide association studies, single nucleotide polymorphisms (SNPs) in the VitD binding protein (GC) and VitD metabolic hydroxylases were found to influence serum VitD levels. While it is known that genetic factors are responsible for a significant degree of variability in serum VitD levels in Caucasian twins with multiple sclerosis, it is currently unclear whether these polymorphisms influence VitD concentrations in Singapore IBD patients. Hence, the study aims to evaluate the association between GC and VitD metabolic hydroxylases SNPs with serum VitD levels in Singapore Chinese IBD patients. Methods: A prospective study was conducted at Singapore General Hospital Outpatient IBD Centre over 1-year period from July 2014 to July 2015. Serum 25(OH)D concentration was measured using radioimmunoassay. DNA was isolated from blood sample and Taqman assays were used to genotype 2 SNPs (rs7041 and rs4588) in the GC gene and 3 SNPs (rs12785878 in DHCR7/NADSYN1, rs10741657 in CYP2R1, rs6013897 in CYP24A1) belonging to VitD metabolic hydroxylases. Hardy-Weinberg equilibrium was tested using Pearson's χ 2 test. The association between the GC and VitD metabolic hydroxylases SNPs on serum VitD levels was analyzed using Student's t -test. SPSS version 16.0 software was used to perform data analysis and results were considered statistically significant when P < 0.05. Results: A total of 29 IBD Chinese patients (12 CD; 17 UC) were recruited. Genotyping was successfully performed in all patients. The reliability and reproducibility of genotyping was confirmed using DNA samples from 62 Chinese healthy volunteers enrolled. No deviation from Hardy-Weinberg equilibrium was observed for all 5 SNPs. Among the 5 SNPs investigated, DHCR7/NADSYN1 gene polymorphism (rs12785878) showed a significant association with serum VitD levels in CD and UC patients respectively ( P < 0.05). In these CD patients, those homozygous or heterozygotes for the risk allele (GG/GT) had significantly lower serum VitD level (19.5 ± 3.83 ng/mL, n = 9) compared with those homozygotes for the non-risk allele (TT) (27.3 ± 5.6 ng/mL, n = 3) in the dominant model. On the other hand, UC patients who are homozygotes for the risk allele (GG) had significantly lower serum VitD level (17.4 ± 5.6 ng/mL, n = 9) compared to those heterozygotes or homozygotes (GT/TT) for the non-risk allele (25.5 ± 9.6 ng/mL, n = 8) in the recessive model. One of the GC SNPs (rs7041) was also found to be significantly associated with serum VitD levels in the UC patients ( P = 0.018). UC patients homozygous for risk allele (AA) at rs7041 had lower serum VitD level (17.7 ± 6.5 ng/mL, n = 11) compared with heterozygotes (AC) (27.5± 8.7 ng/mL, n = 6). Conclusions: Significant association between serum VitD levels and SNPs in the VitD metabolic pathway was observed in Singapore Chinese IBD patients. DHCR7/NADSYN1 (rs12785878) and GC (rs7041) genes have significantly influenced circulating serum VitD levels, contributing to lower serum VitD levels in this population.